Tea Tourism and its Impacts on Ethnic Marriage and Labor Division. Issue 4 (2nd October 2018) - Lin, Qingqing; Wen, Julie Jie
ABSTRACT: Profound changes have been identified in the ethnic tea regions of Yunnan Province, southwest China, with the influence of tourism and the tea economy. The tea industry and tea tourism provide special opportunities for females. This research captures the characteristics of the changes in family and labor division. Empirical data were collected between 2006 to 2016 from in-depth interviews and focus groups on ethnic females. This research indicates that the intermarriage radius of local people is greater than ever before, as local people have more and wider encounters. Marriage provides a pathway for people from diverse backgrounds to complement each other. Both male and female play important roles. Although some women are more sociable and adventurous, and they are responsible for expanding business, other females prefer to take home-based duties. The dynamics of power in gender relationships has evolved significantly with the influence of tea and tourism. Tea tourism provides a platform for individual development within the social evolution. This article reflects the swift changes in remote Yunnan, where gender roles, the tea industry and social changes are interwoven. The research is significant in exploring changes in ethnic marriage and labor division based on tea resources.